2017
DOI: 10.1038/s41598-017-13809-y
|View full text |Cite
|
Sign up to set email alerts
|

The protein phosphatase 1 regulator NIPP1 is essential for mammalian spermatogenesis

Abstract: NIPP1 is one of the major nuclear interactors of protein phosphatase PP1. The deletion of NIPP1 in mice is early embryonic lethal, which has precluded functional studies in adult tissues. Hence, we have generated an inducible NIPP1 knockout model using a tamoxifen-inducible Cre recombinase transgene. The inactivation of the NIPP1 encoding alleles (Ppp1r8) in adult mice occurred very efficiently in testis and resulted in a gradual loss of germ cells, culminating in a Sertoli-cell only phenotype. Before the over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 61 publications
(65 reference statements)
6
25
0
Order By: Relevance
“…In contrast, the liver-specific NIPP1 KO showed a rather mild phenotype associated with bile-duct hyperplasia through enhanced biliary epithelial cell proliferation [112]. Collectively, the NIPP1 mouse models indicate that the functions of NIPP1 may be cell-type dependent [107,108,112]. NIPP1-null embryos at embryonic day E6.5 showed increased global phospho-threonine signals [113], in line with a substrate-specifying role of NIPP1 (Table 3) [26,110].…”
Section: Cellular-context Dependent Functions Of Nipp1mentioning
confidence: 90%
See 2 more Smart Citations
“…In contrast, the liver-specific NIPP1 KO showed a rather mild phenotype associated with bile-duct hyperplasia through enhanced biliary epithelial cell proliferation [112]. Collectively, the NIPP1 mouse models indicate that the functions of NIPP1 may be cell-type dependent [107,108,112]. NIPP1-null embryos at embryonic day E6.5 showed increased global phospho-threonine signals [113], in line with a substrate-specifying role of NIPP1 (Table 3) [26,110].…”
Section: Cellular-context Dependent Functions Of Nipp1mentioning
confidence: 90%
“…NIPP1, encoded by the Ppp1r8 gene, is a major nuclear PIP that is ubiquitously expressed, but its expression level is cell-type dependent [107,108]. The N-terminal forkhead-associated domain of NIPP1 recruits PP1 substrates that are phosphorylated at threonine-proline dipeptide motifs, including the pre-mRNA splicing factor SAP155 and the methyltransferase EZH2 [38,94,109,110].…”
Section: Cellular-context Dependent Functions Of Nipp1mentioning
confidence: 99%
See 1 more Smart Citation
“…The animals were sacrificed 2 weeks from the beginning of this treatment, when they reached the age of 6 weeks. At this stage, a histological phenotype cannot yet be discerned in the iKOs (27). However, the NIPP1 protein level in their testis was already reduced by about 70%, as compared with its level in CTR mice (Fig.…”
Section: The Ablation Of Nipp1 In Testis Results In a Loss Of Prc2 Comentioning
confidence: 89%
“…Using an inducible NIPP1 knockout (iKO) model, we have demonstrated that NIPP1 is essential for mammalian spermatogenesis and, more specifically, is required for the transcriptional regulation of genes implicated in germ cell proliferation and survival (27). In this study, we used this iKO model to show that the deletion of NIPP1 in testis is associated with the loss of EZH2 and a reduced histone H3K27 trimethylation at target genes.…”
mentioning
confidence: 99%